Profil Kimia Klinik Darah Sapi Bali (BLOOD CLINICAL CHEMISTRY PROFILES OF THE BALI CATTLE) - Kendran, Anak Agung Sagung; Damriyasa, I Made; Dharmawan, Nyoman Sadra; Ardana, Ida Bagus Komang; Anggreni, Luh Dewi (Jurnal Veteriner; Vol 13 No 4 (2012), 2013)
For the evaluation of clinical tests in veterinary laboratories a reference basis of normal values ofclinically healthy farm animals is essential. It is well known that variables such as breed, age and sex havean influence on many blood parameters. The reference value of blood chemistry of bali cattle is scanty. Theaim of the current study was to evaluate blood chemistry of bali cattle includes alanine aminotransferase(ALT), aspartate aminotransferase (AST), urea, creatinine and glucose, measured by an auto analyzer.These data were used to establish reference intervals in bali cattle of different ages and sex. Blood wascollected from 195 (21 young males, 54 adult males, 60 young females, and 60 adult females) clinicallyhealthy bali cattle by means of jugular venipuncture. Values from different age and sex were comparedstatistically. The results of the study was obtained that ALT and blood glucose significantly higher inmales Bali cattle (P <0.05) then in females. ALT, AST and urea were significantly higher in adults Balicattle (P<0.05) then in young Bali cattle. However, glucose of young Bali cattle was higher when comparedwith the adult. There was no significant difference in the creatinine levels between adults and the youngones. The results of the current study provide reference intervals for clinical chemistry of Bali cattle
Keywords: Bali cattle, Clinical chemistry